2019
DOI: 10.1136/bjophthalmol-2019-314293
|View full text |Cite
|
Sign up to set email alerts
|

Congenital monocular elevation deficiency associated with a novelTUBB3gene variant

Abstract: BackgroundThe genetic basis of monocular elevation deficiency (MED) is unclear. It has previously been considered to arise due to a supranuclear abnormality.MethodsTwo brothers with MED were referred to Leicester Royal Infirmary, UK from the local opticians. Their father had bilateral ptosis and was unable to elevate both eyes, consistent with the diagnosis of congenital fibrosis of extraocular muscles (CFEOM). Candidate sequencing was performed in all family members.ResultsBoth affected siblings (aged 7 and 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 14 publications
0
9
0
Order By: Relevance
“…The pedigrees and characteristics of individuals diagnosed with CFEOM are shown in Figure 1 A and Supplementary Table S1 , respectively. The phenotypes and genotypes associated with families F1 [ 8 ] and F4 [ 15 ] and subject S1:II-1 [ 4 , 16 ] have previously been described.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The pedigrees and characteristics of individuals diagnosed with CFEOM are shown in Figure 1 A and Supplementary Table S1 , respectively. The phenotypes and genotypes associated with families F1 [ 8 ] and F4 [ 15 ] and subject S1:II-1 [ 4 , 16 ] have previously been described.…”
Section: Resultsmentioning
confidence: 99%
“…Affected subjects in F1 had significant intra-familial clinical variability and each harbored a heterozygous TUBB3 mutation (c.1263G > C, p.Glu421Asp) [ 8 ]. Subject F1:I-1 had bilateral blepharoptosis, left esotropia, and bilateral restriction on elevation ( Figure 1 B); however, both his children (F1:II-1 and F1:II-2) had unilateral restriction without ptosis ( Figure 1 B) [ 8 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Affected individuals frequently present additional neurological signs and symptoms in addition to mental abnormalities in CFEOM-3 [ 12 ]. Recently, Thomas et al suggested that some patients diagnosed with congenital monocular elevation deficiency could be included in CFEOM-3 [ 13 ]. CFEOM-4, also known as Tukel syndrome, is characterized by a CFEOM-3 phenotype plus hand oligodactyly [ 14 , 15 ].…”
Section: Cfeom Subtypesmentioning
confidence: 99%
“…The limitation of eye movement in CFEOM3 patients is so various that they range from no or mild to severe ophthalmoplegia and may also show a unilateral or asymmetric presentation [ 21 ]. Interestingly, a recent study showed that the TUBB3 gene variant could cause congenital monocular elevation deficiency [ 22 ]. MCD includes lissencephaly (agyria–pachygyria), polymicrogyria or polymicrogyria-like cortical dysplasia, and cortical gyral simplification.…”
Section: Introductionmentioning
confidence: 99%